In-vitro effect of nimbolide, an isoprenoid of neem leaf, on antioxidant system of rat cauda epididymal spermatozoa: A dose dependent study - Shashidhar B. Kumbar, Umadevi C. Jadaramkunti, Ravindranath H. Aladakatti (Journal of Applied Pharmaceutical Science)
The present in vitro study aims to address the possible evaluation of nimbolide, a major component of neem leaves, on the antioxidant system of rat spermatozoa to promote oxidative stress in a dose-dependent manner. To assess the effect of the nimbolide on activities of superoxide dismutase (SOD), catalase, Glutathione reductase (GR), Glutathione peroxidase (GPx), a-Glucosidase, production of Hydrogen peroxide (H2O2) and level of lipid peroxidation (LPO) in rat spermatozoa, increasing quantities 0.5 mM, 1 mM, 1.5 mM and 2.0 mM per ml of the nimbolide was added to the cultured medium prior to the addition of cauda epididymal spermatozoa. The spermatozoa were observed at 6th h post-culture and the expressions of enzyme activities and production of H2O2, level of LPO were recorded. The activities of antioxidant enzymes decreased significantly while the levels of H2O2 generation and LPO increased significantly in nimbolide treated spermatozoa in a dose dependent manner when expressed in terms of milligram protein and milligram DNA. The activity of a- glucosidase, a negative control against antioxidant enzymes, did not show any significant change at any of the doses. The results suggest that graded doses of nimbolide elicit depletion of antioxidant defense system in sperm, indicating nimbolide-induced oxidative stress in the epididymal sperm of rats.
Keywords: Nimbolide, Antioxidant enzymes, Cauda epididymal spermatozoa Oxidative stress, Lipid peroxidation and Rats